Targeting autophagy promotes the antitumor effect of radiotherapy on cervical cancer cells - Fanjie Meng; Ying Yan; Li Zhou; Song Zhao; Lingyan Sun; Huiying Yu (Cancer Biology & Therapy)
Radiotherapy is the mainstay of cancer treatment, and reducing radioresistance is still a poorly explored issue in radiotherapy. Our study was designed to explore the possible functions and mechanisms of autophagy in cervical cancer cells treated with radiotherapy. We discovered that autophagy was activated in C33a and HeLa cervical cancer cells in parallel with increased apoptosis and formation of polyploid giant carcinoma cells (PGCCs) after radiation. Inhibition of autophagy significantly enhances radiation-induced cytotoxicity and apoptosis in cervical cancer cells and reduces PGCCs formation. Immunoblot analysis, as part of the mechanistic experiments, showed that the phosphorylation levels of Akt, mTOR, and P70S6K were downregulated. Thus, our research demonstrated that inhibiting autophagy enhances the antitumor effects of radiation on cervical cancer cells.